2011
DOI: 10.33899/rden.2011.45472
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Facial Heights Between Iraqi Arab and Kurdish

Abstract: Aims: To investigate for any difference in facial height measurements between Iraqi Arabs and Kurds adolescents. Materials and Methods: lateral cephalometric radiographs Of 42Arabic adolescents in Mosul city and 43 Kurdish adolescents in Arbil city were assessed for anterior and posterior facial height measurements. Results: No significant difference was found in facial height measurements between Arabic males and females. In Kurds, males showed significantly higher facial measurements than females. Kurdish ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…The x-ray images used in this study were taken from orthodontics clinics located in different parts of Baghdad city. The Cephalometric measurement of Jarabak's analysis is illustrated in Figure (10). In this study, the region of head in images of X-rays was identified, with known x-y coordinates for five points having all the features needed in the calculations.…”
Section: Materials and Methods:-mentioning
confidence: 99%
See 2 more Smart Citations
“…The x-ray images used in this study were taken from orthodontics clinics located in different parts of Baghdad city. The Cephalometric measurement of Jarabak's analysis is illustrated in Figure (10). In this study, the region of head in images of X-rays was identified, with known x-y coordinates for five points having all the features needed in the calculations.…”
Section: Materials and Methods:-mentioning
confidence: 99%
“…The values of the variables can be practically anything; real or integer numbers, Boolean values or strings, for example. The actual model is the set of functions that describe the relations between the different variables [10].…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation